Pemanfaatan Activated Carbon dalam Meningkatkan Fungsi Koagulan untuk Pengolahan POME (Palm Oil Mill Effluent) - Stefany, Cindy (Journal of Bioprocess, Chemical and Environmental Engineering Science, 2022)
POME is a colloidal suspension containing 95-96% water, 0.6-0.7% oil and 4-5% total fat and solids. POME waste treatment is carried out development by a combined method of adsorption and coagulation. This study aims to determine variations in the concentration of activated carbon and coagulants against the removal of COD and TSS from POME treatment water discharges and determine the optimum conditions of the combined process of adsorption and coagulation to the reduction of the resulting COD and TSS concentrations. POME materials are measured first pH, TSS and COD values before being treated. POME treatment with a combined method of adsorption and coagulation is carried out by adding activated carbon (3; 6; 9 mg / L) and PAC (0.2; 0.55; mg / L) at room temperature (25 ° C) for 20 minutes for the adsorption process and 1 minute for the coagulation process. The contact time lasts for 30 minutes, the optimization of process conditions is determined by response surface methodology (RSM). Parameters tested include TSS and COD levels. The factor that has the most significant influence on the COD response is activated carbon levels, and the factor that has the most significant influence on the TSS response is PAC. Optimum process conditions were obtained at activated carbon levels of 9 mg / L and PAC of 0.69 mg / L with a response of COD 430.272 mg / L and TSS 297.941 mg / L.